Description of polimorfism FTO Gene (Fat and Mass Obesity associated) rs9939609 on Obesity and Non Obesity Subject - Sayekti, Fitria Diniah Janah; Marfianto, Alfian (Al-Hayat: Journal of Biology and Applied Biology, 2023)
Obesity is a major risk factor for several chronic diseases and is a major health and economic burden on society. The FTO gene (Fat and Mass Obesity associated) was identified as a gene that has an influence on the incidence of obesity according to Genome-wide Association Studies. Examination of the FTO gene polymorphism rs9939609 using 15 samples of obese subjects and 15 samples of non-obese subjects at Prodia Pusat Jakarta employees. This study used descriptive research to describe the polymorphism or variation of the FTO (Fat mass and obesity-associated) gene rs9939609 in obese and non-obese objects among Prodia Pusat Jakarta employees. In this study, non-obese subjects obtained 100% AT allele results. This indicates that genetically there is a potential risk factor for obesity. In obese subjects, 60% of the TT alleles were found. Genetically it should not be a risk allele for the risk of obesity. This can be caused by lifestyle or diet. In this study, an AA allele of 6.67% was found, indicating a greater risk of obesity. From the study, it was concluded that the percentage of the FTO gene polymorphism rs9939609 in obese and non-obese subjects in Prodia Pusat Jakarta employees was the AT allele 100% for obese subjects and for obese subjects. non-obese subject of 33.33%. The AA allele is 6.67% for obese subjects, and the TT allele is 60% for obese subjects.